Intravascular Mesenchymal Stromal/Stem Cell Therapy Product Diversification: Time for New Clinical Guidelines - Moll, Guido; Ankrum, James A.; Kamhieh-Milz, Julian; Bieback, Karen; Ringdén, Olle; Volk, Hans-Dieter; Geissler, Sven; Reinke, Petra (Trends in molecular medicine, 2019)
Intravascular infusion is the most popular route for therapeutic multipotent mesenchymal stromal/stem cell (MSC) delivery in hundreds of clinical trials. Meta-analysis has demonstrated that bone marrow MSC infusion is safe. It is not clear if this also applies to diverse new cell products derived from other sources, such as adipose and perinatal tissues. Different MSC products display varying levels of highly procoagulant tissue factor (TF) and may adversely trigger the instant blood-mediated inflammatory reaction (IBMIR). Suitable strategies for assessing and controlling hemocompatibility and optimized cell delivery are crucial for the development of safer and more effective MSC therapies. MSC products have largely diversified during the past decade, making extrapolation about safety and efficacy from first-generation products inappropriate. MSCs and other blood non-resident cellular therapeutics display different degrees of incompatibility with human blood, which compromises their safety and efficacy. TF is the major determinant of cell product hemocompatibility, and this should be routinely monitored in all therapeutics intended for intravascular delivery. MSC products from different tissue sources display high variability in TF expression, with potential lethal consequences for patients when infused systemically. Once aware of the problem, a large array of product and process innovations became available to improve the clinical delivery of systemically infused cellular therapeutics.